Effect of Relaxation on Insomnia during Third Trimester among Pregnant Women - Aghdas Malekzadegan; Maryam Moradkhani; Hassan Ashayeri; Hamid Haghani (Iran University of Medical Sciences, 2010)
Background and Aim : Insomnia is one of the most prevalent disorders of pregnancy that can results in many problems before, during and after delivery. Insomnia management should be attempted to provide comfort during pregnancy. The aim of study was to determine the effect of relaxation on insomnia during third trimester among pregnant women.   Material and Method : This was a randomized field trial in which 95 pregnant women, referred to Health and Medical Center in Zanjan and were diagnosed to suffer from insomnia, were randomly assigned to either experimental (n=47) or control (n=48) group. Control group only received routine educationa, but participants in experimental group were trained in relaxation over two sessions and were given a hand out reviewing the relaxation procedure, relaxation log for recording home practice and tape-recorded version of the relaxation. The relaxation treatment lasted 4 weeks.   Results : Findings showed that relaxation reduced insomnia intensity in 80.9% of the women in experimental group (P≤0.0001) and also alleviated insomnia in 51.1% of them (P≤0.0001)   Conclusion : It can be concluded that insomnia is common in late pregnancy and relaxation can be considered effective in treatment of insomnia. Providing education about relaxation for treatment of insomnia during third trimester is recommended.